Effect on the pregnancy, prolactin and sex hormones in rats of methanol subextract of lea ves of Tagetes filifolia "anisillo" - Bonilla R., Pablo (2008)
Tagetes filifolía a medicinal Asteraceae according to data by ethnobotany show the uses to alleviate aliments of the digestive tract, for the secretion of lactic and fertility. Stressful environmental factors are causing an increase in fertility problems, so it is necessary to look for products that regulate fertility, that improve spermatogenesis and ovulation. Was detected the effect or the components of the methanol subextract of leaves of anisillo on fertilitv in rats, using the rnethod of Rani Srivastava S. et al (2004) with modifications. 36 normal rats strain Holtzmann 150 + 20 g adquired by the NIH, were distributed randomly into three groups of 12 animals, six males and six females, together since the beginning of the administration of substances, orally for 18 days: Group 1, saline 2 mL / kg; group_2, anisillo 200 mg / kg, and Grup03 metoclopramide 1;:, mg / kg; evaluation indicators were in males: Testosterone expressed as ng / dL in females: the stat¡; of pregnancy, prolactin (ng /ml), estrogen (pg / mI), progesterone (ng / mi). The subextract of anisillo administered in male rats shO\"\'ed minar variations of testosterone (p <0418); in females: there were more pregnant rats (p <0022), the size of fetuses or the ad vancement of the state of pregnancy was higher (p <0009), there \"vere increascs estrogens, progesterone and prolactin. To increase the pregnancy of female rats treated with the subextract of anisillo, was detected flavonoids and alkaloids which may have allowed the improvement of spermatogenesis and ovulation.